Agenda for a new economy : from phantom wealth to real wealth - Korten, David C (A BK currents book, 2010)
In this revised and updated edition, David Korten has fleshed out his vision of the alternative to the corporate Wall Street economy: a Main Street economy based on locally owned,, community-oriented living enterprises whose success is measured as much